Letter from Max Bredig to Georg Bredig, October 31, 1938 - Bredig, Max Albert (1938)
Max Albert Bredig (1902-1977) updates his father, Georg Bredig (1868-1944) on his search for a job in the United States of America. He mentions scientists such as Ernst Cohen (1869-1944), James W. McBain ( 1882-1953), and Ernst Berl (1877-1946), who will help him.
Keywords: Bredig, Max Albert, 1902-1977; McBain, James William, 1882-1953; Cohen, Ernst, 1869-1944; Berl, Ernst, 1877-1946; Chemists; Job hunting; Bredig, Georg, 1868-1944